2021
DOI: 10.3389/fpos.2021.660607
|View full text |Cite
|
Sign up to set email alerts
|

The Personalization of Politics in Anglo-American Democracies

Abstract: In American politics, few argue with the idea that leaders matter: in the 2020 American election, the media closely tracked the performance and activities of Joe Biden and Donald Trump, for example, suggesting to us that who they are matters. Voters indicate on their ballot which presidential candidate they prefer, marking an x next to the person’s name, giving further credence to the idea that the individual matters in the process. Contemporary Anglo-Westminster-style democracies have many things in common wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Party leaders are fundamental actors in parliamentary democracies and definitely one of the most covered by the media (Aarts et al, 2011). Moreover, leaders' evaluations are central to the vote choice of many citizens in Western democracies, albeit that it is unclear whether this influence has increased over the years (Garzia et al, 2020;Bittner, 2021). Importantly for our argument, recent studies have shown that citizens assess more positively leaders who share their sociodemographic characteristics, such as their age (Sevi, 2021), gender (Dassonneville et al, 2021) and the proximity of their geographical residency (Put, 2021).…”
Section: The Role Of Women Representatives and Leadersmentioning
confidence: 77%
“…Party leaders are fundamental actors in parliamentary democracies and definitely one of the most covered by the media (Aarts et al, 2011). Moreover, leaders' evaluations are central to the vote choice of many citizens in Western democracies, albeit that it is unclear whether this influence has increased over the years (Garzia et al, 2020;Bittner, 2021). Importantly for our argument, recent studies have shown that citizens assess more positively leaders who share their sociodemographic characteristics, such as their age (Sevi, 2021), gender (Dassonneville et al, 2021) and the proximity of their geographical residency (Put, 2021).…”
Section: The Role Of Women Representatives and Leadersmentioning
confidence: 77%
“…The concept of presidentialization of parliamentary systems stresses increasingly leadershipcentred electoral processes and personalized party campaigns (Poguntke & Webb, 2005). Correspondingly, Bittner (2011Bittner ( , 2018 has empirically demonstrated that voters' perceptions of party leaders, in particular the leaders' traits and personality, affect voter decisions and the distribution of votes in elections (see also Garzia, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In empirically testing the personalization thesis, claiming that party leaders have become more important to voters over time, Bittner (2018) concludes that party leaders and their personality have always been important in the minds of the electorate; voters have constantly evaluated party leaders and considered them in their vote calculus. However, what is new, Bittner notes, is that the amount of and access to information about the personality of party leaders is increasing, particularly on the web and in social networking sites and apps (Bittner, 2018, p. 53).…”
Section: Introductionmentioning
confidence: 99%